The Factors Influencing Consumer Behavior Decision to Purchase Products in Walking Street Market in Chengdu City, China - Yang, Chi; Putachote, Nitipon (Prosiding University Research Colloquium, 2025)
This study examines the factors influencing consumer purchase decision-making in the Walking Street Market of Chengdu, China, focusing on demographic characteristics and the Marketing Mix 7Ps (Product, Price, Place, Promotion, People, Process, and Physical Evidence). A quantitative survey methodology was employed, with data collected from 450 consumers through structured questionnaires using convenience sampling. The collected data were analyzed using descriptive statistics (e.g., mean, standard deviation) and inferential statistics (e.g., t-tests, ANOVA, and multiple regression) to test the hypotheses at a 95% confidence level. The results indicate that age and education significantly impact purchase decisions, while gender, occupation, and monthly income show no significant effects. Among the 7Ps, Product, Price, Place, and Physical Evidence exhibit significant positive influences on purchase decisions, whereas Promotion, People, and Process are not significant. The findings provide practical recommendations for vendors and market managers to optimize marketing strategies and enhance consumer purchase intentions and market competitiveness.